Development, validation and reliability testing of 'Perinatal Bereavement Care Confidence Scale (PBCCS)'. Issue 4 (July 2020) - Kalu, Felicity Agwu; Larkin, Philip; Coughlan, Barbara
Abstract: Background: Equipping midwives and nurses with confidence to provide bereavement care to parents who have experienced a perinatal loss is vital and impacts on the efficacy of the care received by grieving parents. In education and clinical practice environments there are shortages of bereavement care questionnaires specifically designed to measure midwives' and nurses' confidence and psychosocial factors that impact on their confidence to provide bereavement care. Aim: The purpose of the study was to develop a valid and reliable perinatal bereavement care confidence scale (PBCCS). Methods: The PBCCS was developed in 4 phases. Phase 1: Questionnaire development, 44 questions were formulated from the literature. Phase 2: Face and content validation of the PBCCS by an Expert Panel. Phase 3: A pilot study was conducted and included 10 cognitive pre-testing interviews and test-retest reliability assessment with a cohort of 26 midwives. Phase 4: Construct validity was assessed using factor analysis with 277 midwives and nurses. In order to avoid confusion with terminologies, the term midwife was used for both nurses and midwives who provided care to bereaved parents and participated in the study. Internal consistency reliability measurement was assessed with Cronbach's alpha. Ethical approval of the study was obtained from four maternity hospitals in Ireland. Results: The PBCCS has 43 items. Bereavement care knowledge (15 items, 3 sub-scales). Bereavement care skills (9 items, 2 sub-scales). Self-awareness (8 items, 2 sub-scales). Organisational support (11 items, 2 subscales). The internal consistency reliabilities ranged from 0.753 to 0.871 except for one subscale 0.663. Conclusions: The PBCCS is a valid and reliable tool with good psychometric properties which can be used to measure midwives' confidence and the psychosocial factors thatimpact on their confidence to provide bereavement care.